Exacerbation of symptoms, nocturnal acid reflux, and impaired autonomic function are associated with sleep disturbance in gastroesophageal reflux disease patients - Huang, Yizhou; Liu, Jie; Xu, Linsheng; Qi, Wu; Dai, Jie; Wang, Bo; Tian, Jiashuang; Fu, Xin; Yu, Yue (Frontiers in Medicine, 2024)
Background & Aim: Gastroesophageal reflux disease (GERD) patients often report sleep disturbance (SD); however, the relationship between GERD and SD is unknown. This study investigated whether SD affects symptoms, acid reflux, and autonomic function in GERD patients.Methods: A total of 257 subjects (126 patients with SD and 99 patients without SD) participated in this survey from January 2020 to August 2022. Participants were required to complete questionnaires including the GERD impact scale (GIS), Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD). Esophageal mucosal injury, acid exposure, peristaltic function and autonomic function were assessed by upper endoscopy, high-resolution esophageal manometry (HRAM), 24-hour multichannel intraluminal impedance with pH (24h-MII-pH) and electrocardiography (ECG).Results: GERD patients with SD experienced a higher frequency of prolonged reflux (P < 0.001), longest reflux event (P < 0.001), acid exposure time (P < 0.001) during the recumbent period, and a higher incidence of erosive esophagitis (EE) (59.5% vs. 45.5%, P = 0.036) than those without SD. Pearson's correlation analysis showed that SD was positively correlated with GIS (r = 0.725, P < 0.001), HAMA (r = 0.680, P < 0.001) and HAMD (r = 0.323, P < 0.001) scores, and negatively correlated with parasympathetic or vagal nerve activity (r = -0.770, P < 0.001).Conclusions: GERD patients with SD experience more severe reflux symptoms and nocturnal acid reflux, which may be related to autonomic dysfunction.